(untitled) (International Conference on Economics, Business, and Management Research (ICEBMR), 2024)
This research aims to determine: 1) the influence of E-WOM, celebrity endorsement, and customer reviews simultaneously on purchasing interest. 2) the partial influence of E-WOM, celebrity endorsement, and customer reviews on purchasing interest. The sampling technique was carried out using purposive sampling with 100 respondents who met the criteria. The data analysis techniques in this research are descriptive analysis, validity test, test rehabilitation, classical assumption testing, and multiple linear regression analysis using the IBM SPSS Statistics 25 application program. Descriptive analysis is a data analysis method carried out to see a picture of research variables, without carrying out hypothesis testing. Validity and reliability tests were carried out to test the device. The classic assumption test is a test of the feasibility of a multiple linear regression model which used to test data quality. Multiple linear regression analysis is a regression model that involves more than one independent variable. The research results show that: 1) E-WOM, celebrity endorsement, and customer reviews simultaneously influence purchasing interest. 2) E-WOM, celebrity endorsement, and customer reviews partially influence purchasing interest.